Kant’s project of eternal peace and its transformation in the teaching of I. G. Fichte - Rumyantseva, Tatyana G. (Journal of the Belarusian State University. Sociology, 2023)
The ideas of those thinkers which should be considered as a philosophical and worldview justification of peace and security acquire undoubted relevance. The purpose of this article is to identify the essence of Kant’s views on the problems of peace and war at different periods of his work, as well as to analyse the process of their transformation in the teaching of his closest follower, I. G. Fichte. The evolution of I. Kant’s ideas about peace and war was revealed, it is shown that the philosopher revises his attitude to the possibility of achieving eternal peace and expresses previously rarely mentioned in the literature about him, positive assessments of war. I. G. Fichte came to recognise the need to wage not only fair liberation wars and to conclude that the eternal peace is not feasible.